Persepsi Konsumen atas Merek Lokal dan Asing Pada Kategori Produk Hedonik dan Utilitarian - Kussudyarsana, Kussudyarsana (Benefit: Jurnal Manajemen dan Bisnis, 2016)
The objective of the research is to examine the relationship between perception of local and foreign brand toward quality product and price dimension. In order to investigate the perception toward local and foreign branding, this study usedÂ  hedonic and utilitarian product. This research used questionnaire to obtain the data. One hundred samples through convinience sampling were used in this research. The result indicate that foreign brand was high score in the perception of quality and price. Â The study also found that there was significance differences of perception of price among local and foreign brand.